Augmented Respiratory–Sympathetic Coupling and Hemodynamic Response to Acute Mild Hypoxia in Female Rodents With Chronic Kidney Disease - Saha, Manash; Sun, Qi-Jian; Hildreth, Cara M.; Burke, Peter G. R.; Phillips, Jacqueline K. (Frontiers in Physiology, 2021)
Carotid body feedback and hypoxia may serve to enhanced respiratory-sympathetic nerve coupling (respSNA) and act as a driver of increased blood pressure. Using the Lewis Polycystic Kidney rat (LPK) model of chronic kidney disease, we examined respSNA in adult female rodents with CKD and their response to acute hypoxia or hypercapnia compared to Lewis control animals. Under urethane anaesthesia, phrenic nerve activity, splanchnic sympathetic nerve activity (sSNA) and renal sympathetic nerve activity (rSNA) were recorded under baseline conditions, and during mild hypoxic or hypercapnic challenges. At baseline, tonic SNA and blood pressure were greater in female LPK rats vs. Lewis rats (all P < 0.05) and respiratory-coupled SNA (respSNA) was at least 2-fold larger (area under curve (AUC), sSNA: 7.8 ± 1.1vs. 3.4 ± 0.7µV.s, rSNA: 11.5 ± 3 vs. 4.8 ± 0.7 µV.s, LPK vs. Lewis, both P < 0.05). Mild hypoxia produced a larger pressure response in LPK (∆MAP 30 ± 6 vs. 12 ± 6 mmHg) and augmented respSNA (∆AUC, sSNA: 8.9 ± 3.4 vs 2 ± 0.7 µV.s, rSNA: 6.1 ± 1.2 vs.3.1 ± 0.7 µV.s, LPK vs. Lewis, all P ≤ 0.05). In contrast, central chemoreceptor stimulation produced comparable changes in blood pressure and respSNA (∆MAP 13 ± 3 vs. 9 ± 5 mmHg; respSNA ∆AUC, sSNA: 2.5 ± 1 vs 1.3 ± 0.7 µV.s, rSNA: 4.2 ± 0.9 vs. 3.5 ± 1.4 µV.s, LPK vs. Lewis, all P > 0.05). These results demonstrate that PKD female rats at baseline exhibit heightened respSNA coupling that is further augmented by mild hypoxia, and not by hypercapnia. This mechanism may be a contributing driver of hypertension in this animal model.